2017
DOI: 10.3892/br.2017.943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and treatment of gastric metastasis from other malignancies of solid organs

Abstract: Abstract. The aim of the present study was to analyze the clinicopathologic features and treatment outcomes of gastric metastasis from other malignancies of solid organs. A review was conducted of patients with metastatic tumors in the stomach from other malignancies of solid organs detected endoscopically at the Department of Surgery, Kochi Medical School, from January 1991 to December 2015. Seven patients (four men and three women), with a median age of 64 years (range, 42-71 years), had metastatic gastric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Gastric involvement by metastatic breast cancer is a rare clinical diagnosis. Furthermore, invasive lobular breast carcinoma is less likely to involve the gastrointestinal tract compared with invasive ductal carcinoma, with the most frequent metastatic sites being the bone, gynecological organs, peritoneum and retroperitoneum (3)(4)(5). In this respect, the present case highlights the importance of considering metastatic tumor of the stomach secondary to invasive lobular carcinoma of the breast, and the importance of immunohistochemical analysis, such as staining for estrogen and progesterone receptors (2,3,5,6).…”
Section: Discussionmentioning
confidence: 74%
“…Gastric involvement by metastatic breast cancer is a rare clinical diagnosis. Furthermore, invasive lobular breast carcinoma is less likely to involve the gastrointestinal tract compared with invasive ductal carcinoma, with the most frequent metastatic sites being the bone, gynecological organs, peritoneum and retroperitoneum (3)(4)(5). In this respect, the present case highlights the importance of considering metastatic tumor of the stomach secondary to invasive lobular carcinoma of the breast, and the importance of immunohistochemical analysis, such as staining for estrogen and progesterone receptors (2,3,5,6).…”
Section: Discussionmentioning
confidence: 74%
“…Even though the exact mechanism of gastric metastasis has not been described some of the probable pathways include direct tumor invasion, lymphatic spread, hematogenous dissemination, and peritoneal spread. Specifically, during hematogenous dissemination, tumor cells likely become trapped within the submucosa or the serosa which are known to have a rich blood supply [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…With an incidence rate of 0.2–0.7% based on clinical and autopsy reports, gastric metastases are rare whereas primary gastric malignancy is one of the most common cancers worldwide and a leading cause of cancer-related death [ 1 , 2 ]. The most common primary sites of metastases to the stomach as described in the literature are the breast, melanoma, lung, kidney, and esophagus [ 1 , 3 ]. It can be difficult to differentiate primary gastric malignancy from metastatic gastric lesions based on clinical, radiological, endoscopic, and histopathological features.…”
Section: Introductionmentioning
confidence: 99%
“…More studies, similar to that of Dabestani et al [ 20 ], have concluded that complete resection of metastases benefits patients’ overall and cancer-specific survival. In addition, treatment of patients with solitary gastric metastasis shows a good outcome compared with treatment of multiple metastases[ 21 ]. When it is feasible, resection of the solitary gastric metastasis should be performed.…”
Section: Discussionmentioning
confidence: 99%